Interacting With Providers: An Intersectional Exploration of the Experiences of Carers of Aboriginal Children With a Disability. (October 2018) - Green, Anna; Abbott, Penelope; Davidson, Patricia Mary; Delaney, Patricia; Delaney, John; Patradoon-Ho, Patrick; DiGiacomo, Michelle
Intersectionality has potential to create new ways to describe disparities and craft meaningful solutions. This study aimed to explore Aboriginal carers' experiences of interactions with health, social, and education providers in accessing services and support for their child. Carers of Aboriginal children with a disability were recruited from an Australian metropolitan Aboriginal community-controlled health service. In-depth, semistructured interviews were conducted with 19 female carers. Intersectionality was applied as an analytical framework due to the inherent power differentials for Aboriginal Australians and carers for people with a disability. Marginalization and a lack of empowerment were evident in the experiences of interactions with providers due to cultural stereotypes and racism, lack of cultural awareness and sensitivity, and poverty and homelessness. Community-led models of care can help overcome the intersectional effects of these identities and forms of oppression in carers' interactions with providers and enhance access to care.